Glucose promotes epithelial‐mesenchymal transitions in bladder cancer by regulating the functions of YAP1 and TAZ. Issue 18 (17th July 2020) - Li, Shi; Zhu, Hua; Chen, Hongde; Xia, Jianling; Zhang, Fangyi; Xu, Ruoting; Lin, Qi
Abstract: Glucose levels and type 2 diabetes (T2D) are both associated with tumorigenesis and epithelial‐mesenchymal transitions (EMTs). EMTs facilitate bladder cancer (BC) metastasis development, but the mechanism by which high‐glucose levels promote these EMTs in BC remains unclear. Therefore, we sought to elucidate the mechanism underlying EMT promotion due to increased glucose levels. T24 and UMUC‐3 cells were cultured in media containing different glucose concentrations. YAP1, TAZ, GLUT1 and EMT‐associated marker expression was analysed via Western blotting and qPCR. BC cell proliferation and invasion were assessed using MTT and Transwell assays, respectively. A xenograft nude mouse model of diabetes was used to evaluate tumour growth and metastasis in vivo. T2D was positively associated with pathologic grade ( P  = .016) and TNM stage ( P  < .001) in BC. High glucose triggered BC cell proliferation and invasion in both in vitro and in vivo conditions. High‐glucose levels also promoted EMTs in BC cells and increased YAP1 and TAZ expression. YAP1 or TAZ knockdown altered EMT marker expression and decreased GLUT1 expression. Overall, our results suggest that high‐glucose levels promote EMTs in BC cells via YAP1 and TAZ regulation. These effector molecules may be promising therapeutic targets for BC cases comorbid with T2D.